Peculiarities of the distribution and expression dynamics of apoptosis marker Bax in patients with rectal cancer under the influence of neoadjuvant chemoradiotherapy with the usage of nitric oxide precursor - V. V. Golotyuk (Zaporozhye State Medical University, 2015)
The aim of research - to determine the proapoptotic Bax protein expression peculiarities in the intact intestine and tumor of patients with rectal cancer under the influence of neoadjuvant chemoradiotherapy (NHRT), including the polyradiomodification using Ftorafur and Tivortine. Methods and results. Bax expression was determined by immunohistochemistry in biopsy and surgical material before and after NHRT in 21 patients with adenocarcinoma of the rectum stage II-III. It was established that under the influence of NHRT Bax expression level in the intact rectum increased slightly. However, expression of Bax in residual tumor parenchyma loci increased sharply compared with that before treatment, especially after polyradiomodification, thus correlating with the degree of therapeutic pathomorphosis. Conclusion. This indicates the importance of the apoptosis as a mechanism of NHRT antineoplastic action, as well as the feasibility of the polyradiomodification with the usage of nitric oxide precursor.